Pengembangan Multimedia Pembelajaran Berbantuan Canva Materi Energi Kelas III Sekolah Dasar - Sari, Nilam; Putra, M Jaya Adi; Permana, Dede (Jurnal Kiprah Pendidikan, 2025)
This research aims to develop Canva-assisted learning multimedia on energy materials for grade III elementary schools. This Canva-assisted learning multimedia was developed using the Research and Development (R&D) method with the ADDIE development model. Multimedia obtained an average score from media experts of 92.5% with a very valid category, material experts obtained an average score of 84.37% with a very valid category, and linguists obtained an average score of 89.28% with a very valid category. While the practicality of Canva-assisted learning multimedia based on the teacher trial questionnaire obtained a score of 95.83% in the very practical category. Meanwhile, the practicality test on students was carried out in two stages, namely limited trials and extensive trials. In the practicality test, the Canva-assisted learning multimedia obtained a percentage score of 88.16% with a very practical category. From the results of validation and practicality, it can be concluded that Canva-assisted learning multimedia on energy material for class III elementary school is very valid and very practical so that it can be used in learning.